Kedudukan Kurikulum dalam Pendidikan Agama Islam - Achmad, Ghufran Hasyim (YASIN, 2021)
The curriculum as a guide or in carrying out the learning process in educational units in order to achieve the expected educational goals. The purpose of this study is to determine the nature or position of the curriculum in Islamic religious education, by knowing the functions and roles and objectives of the curriculum in Islamic education. This research was conducted using library research methods. Based on the analysis of data sources, it can be concluded that the position of the curriculum in Islamic religious education is the most important aspect of education to achieve learning goals and national education goals. The position of the curriculum in Islamic Religious Education has a very important role in shaping one's personality. In education units, education must understand the curriculum in order to plan goals.